The Impact Of Work Stress And Compensation On Employee Retention At Pt Anzon Autoplaza In Pontianak - Maya Purwaningsih; Fita Kurniasari (UNIVED Press, 2025)
This study investigates the impact of work stress and compensation on employee retention at PT Anzon Autoplaza in Pontianak. As a prominent automotive dealership, PT Anzon Autoplaza has faced challenges related to high employee turnover despite its growth. This research aims to analyze how job stress and compensation affect employee retention and to propose strategies to improve job satisfaction and reduce turnover. A quantitative approach was employed, utilizing surveys and interviews with employees and HR personnel, focusing on data from 2020 to 2023. Results indicate a significant positive correlation between work stress and employee turnover, with inadequate compensation further exacerbating this relationship. The study also found that employees who reported high levels of work stress were more likely to have lower job satisfaction and a higher intention to leave. These findings underscore the need for PT Anzon Autoplaza to address work stressors and enhance compensation packages to improve retention. The insights provided aim to assist PT Anzon Autoplaza in developing effective strategies to stabilize its workforce and enhance overall employee satisfaction.